Effectiveness of Using Flipbook-Based E-Module to Improving the Data Analysis Ability of Beauty Education Students - Afifah, Indah Indi; Ratri, Pramesti Adika; Wulandari, Tati; Prihatin, Muhammad Ridho (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Data analysis skills are very important and needed in various sectors, both in education and the professional world. However, many students face challenges in mastering fairly complex data analysis techniques. One method that is increasingly popular in assisting the learning process is the use of E-Modules. These E-modules provide opportunities for students to learn in a structured and flexible way, and allow the material to be tailored to their individual needs. This study aims to evaluate the effectiveness of the use of E-Modules in improving students' ability to analyze data. This study uses a quantitative descriptive approach and collects data through pre-test and post-test questionnaires. The data obtained were then analyzed using a t-test for two paired samples (paired t-test). The paired T-test is used to measure significant changes in students' data analysis skills as seen from the comparison of pre-test and post-test scores. The results of the study indicate that the use of flipbook-based E-modules has proven effective in improving students' data analysis skills. This is evidenced by the results of the paired t-test which shows a significance value (2-tailed) of 0.000, which is less than 0.05, indicating a significant change in the pre-test and post-test results. Thus, it can be concluded that the use of flipbook-based E-modules has a significant influence on improving students' data analysis skills.